(untitled) (Research, Society and Development, 2023)
The study aimed to know the publications on the formation of the bond between parents and infants admitted to the Neonatal Intensive Care Unit in the last 10 years (2012-2022). An integrative literature review was carried out, based on searches in the Online Search and Analysis System of Medical Literature, Latin American and Caribbean Literature in Health Sciences, Nursing Database, using the descriptors: Link and Therapy Unit Intensive Neonatal connected by the Boolean operator AND, in Portuguese, English and Spanish. Resulting in 17 articles. Three categories were elaborated to present the results: factors that hinder the promotion of the bond; measures that facilitate the parental bond with the infant and; the importance of the health team to strengthen the bond. Through the review, it was possible to understand that the parents of newborns hospitalized in the Neonatal Intensive Care Unit have feelings such as fear, anguish and sadness, which influence the formation and strengthening of the bond. The performance of care by the parents while the infant was hospitalized was highlighted as important in the bonding, in addition, the support of professionals was considered fundamental for the parents to have confidence in carrying out the care.